(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2023)
This study aims to determine detoxification among Indonesian Muslim University students in reducing the use of social media in Makassar, and to determine the impact of detoxification among Indonesian Muslim University students in reducing social media use in Makassar. This type of research is qualitative in the form of descriptive. The results of this study note that doing social media detoxification gets various benefits and also the stability of life for someone who goes through it. Therefore, stable use of social media will produce a directed lifestyle. Based on the research results, students have different reasons why they do social media detoxification, some say that when they want to do social media detoxification, students feel a positive impact, especially on mental health and individual well-being.